Pengelolaan Pembelajaran Anak Usia Dini di Kelompok Bermain Paud Nur-Adzkia Telukjambe Karawang - Olinvia Nur Oktriani; H.Dadang Danugiri; Nia Hoerniasih (UNIB Press, 2022)
Education is a very important thing for every human being that is carried out in all aspects of life. Education is given from an early age so that the values in it can be applied to adulthood. Therefore, good education is education that can be given from an early age. In early childhood education the role of the teacher in managing learning is very important because the teacher has a very close relationship with the child while in the school environment. The aims of this study are to: (1) describe the planning of early childhood learning; (2) Describe the organization of early childhood learning; (3) Describe the implementation of early childhood learning; (4) Describe the supervision of early childhood learning in the Nur-Adzkia PAUD Playgroup Telukjambe Karawang. The method used in this study is a descriptive method with a qualitative approach. The subjects in this study consisted of four subjects, namely one manager, two educators and one student's parent. Data collection techniques in this study were observation, interviews and documentation. And analysis using the steps: (1) data reduction (data reduction), (2) data presentation (data display), (3) drawing conclusions (verification). The results of this study (1) lesson plans are carried out daily, daily, monthly and semester by assessing the way or process of working students; (2) the organization is carried out with the cooperation of educators in preparing learning preparations, implementing learning programs and in accordance with each individual permanently; (3) implementing learning consists of preliminary activities, core activities and closing activities; (4) supervision is carried out by assessing ongoing programs through accreditation every 5 years.Keywords: Management, Learning, Early Childhood Education